2023
DOI: 10.47852/bonviewglce32021340
|View full text |Cite
|
Sign up to set email alerts
|

Green Energy and Technological Innovation Towards A Low-Carbon Economy in Bangladesh

Asif Raihan

Abstract: This study aims to investigate the influences of green energy, technological innovation, economic growth, urbanization, and labor force, on the low-carbon economy in Bangladesh. Bangladesh was chosen for this study as the country in the sixth most vulnerable nation, and the results of climate change on the country's ecology and economy have been devastating. By using yearly data extending from 1990 to 2020, this research employed the autoregressive distributed lag (ARDL) technique to explore the connections be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 70 publications
0
11
0
Order By: Relevance
“…However, from the observations of this study, it is concluded that Bangladesh being a developing nation has recently experienced severe stress due to the negative effects of climate change. Likewise, this statement is endorsed by Raihan (2023a) and in their recent studies. To uphold the country's elevated ecological benchmarks, the government of Bangladesh and other relevant parties must make investments in renewable energy sources.…”
Section: Summary Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…However, from the observations of this study, it is concluded that Bangladesh being a developing nation has recently experienced severe stress due to the negative effects of climate change. Likewise, this statement is endorsed by Raihan (2023a) and in their recent studies. To uphold the country's elevated ecological benchmarks, the government of Bangladesh and other relevant parties must make investments in renewable energy sources.…”
Section: Summary Discussionmentioning
confidence: 70%
“…The primary conclusion drawn from this study is that the economic expansion in Bangladesh is being accompanied by detrimental consequences for the environment. Another study by Raihan (2023a) looked at how Bangladesh's low-carbon economy was affected by technological innovation, green energy, economic expansion, urbanization, and labor force. The ecosystem and economy of Bangladesh have suffered greatly as a result of climate change.…”
Section: Empirical Studies On Green Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that the use of renewable energy and TI would, over time, cause the carbon economy to shrink both in the long run and in the short term [36]. Green energy utilization and technological innovation are found to be the best crucial approaches to maintain environmental sustainability in Bangladesh [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, the findings indicated that a 1 % boost in green energy utilization and technology innovation would result in a 0.21 % and 0.18 % decline in the carbon economy in the long run whereas 0.15 % and 0.10 % drop in the short run, respectively. The outcomes of the investigation demonstrated that economic growth, urbanization, and labor force all impact adversely to accomplish the low-carbon economy, making green energy utilization and technological innovation the best crucial approaches to maintain environmental sustainability [39].…”
Section: Environmental Effectmentioning
confidence: 99%